National directory of civil society resource organizations Philippines. (Series on foundation building in Southeast Asia / the Synergos Institute, 2000)
A directory of CSROs, providing information on the organizations' offices, funding levels sources of funding, program area, services offered and the organizations' mission statements. The directory also features tables showing lists of organizations classified according to their nature(funding, nonfunding or both) and a background study on CSROs- types of funders, geographical locations, expenditures, distribution of support by type of beneficiary, list of CSRO grant making, revenues, endowments, average number of CSRO staff and volunteers, and an analysis of these information in a conclusion.